Quail Management: Issues, Concerns, and Solutions for Public and Private Lands - A Southeastern Perspective - L. Wes Burger (National Quail Symposium Proceedings, 2017)
Biologists generally assume that habitat loss, fragmentation, and conversion resulting from changes in landuse are primarily responsible for the nearly rangewide declines in northern bobwhite (Colinus virginianus) abundance noted since at least 1990. Few data-based analyses have addressed this relationship at broad spatial scales. We used data on northern bobwhite abundance from the North American Breeding Bird Survey (BBS; 1966–1999) and county-level landuse from the U.S. Census of Agriculture (COA; 1978, 1987, 1997) to evaluate how 9 landuse variables related to northern bobwhite abundance at the rangewide spatial scale. We also explored the relationship between cropland cover and northern bobwhite abundance by state, physiographic region, and using a moving window approach. Although northern bobwhite abundance typically decreased at the rangewide spatial scale, trends in abundance varied considerably spatially, either exhibiting no trend or increasing in many western and northern portions of this species’ range. While both spatial and temporal patterns in landuse were obvious, there were no clear univariate or multivariate relationships among these variables and bobwhite abundance that could be applied universally across this species’ range. The relationship between cropland cover and northern bobwhite abundance based on physiographic regions was more interpretable than that based on political boundaries (states). When data were used to define spatial patterns between cropland cover and northern bobwhite abundance, spatially consistent and temporally persistent patterns were obtained. We suggest that further research using moving windows of various dimensions, including landuse variables in addition to cropland, and adding several more decades of bobwhite and landuse data is an essential aspect of formulating defensible, spatially explicit strategies for northern bobwhite conservation and management.
Keywords: abundance; Colinus virginianus; habitat; landscape; landuse; northern bobwhite; spatial scale; trends